The politics of information the case of the European Union - Blom, Tannelie; Vanhoonacker, Sophie; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This collection presents the results of a research agenda which examines how information plays a key role in policymaking. As a very dynamic environment characterized by many different modes of information gathering and processing, the EU forms a particularly interesting case to test the politics of information approach.
Keywords: Political science; Political theory; Democracy; Public policy; European Union; Public administration